2022
DOI: 10.1177/09544054221076628
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of over-bending defect in the cold roll forming of U-channel section using experimental and numerical methods

Abstract: In spite of product quality increase in the cold roll forming process by previous practical researches for defects prevention, there are some ill-considered defects such as over-bending, which diminished the product quality in the open section products of this process. This defect which happens by superfluous bending of sheet in the forming stand not only lead to defective products, but also trigger other defects such as edge wrinkling. Since in an elaborate process such as cold roll forming, forming parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Gao et al [11] designed a set of roll position automatic adjustment system that can predict roll parameters by using PCA-BP algorithm to train roll parameter prediction model, so as to predict roll parameters of newly developed square tube cold roll forming distribution. Bidabadi et al [12] studied the in uence of bend angle increment, ange width, strip thickness, bending radius and material strength on over-bending defect ground by combining multiple groups of test and numerical simulation. Therefore, the appropriate cold roll forming process is also an important guarantee for the precise forming of circular tubes of different speci cations.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [11] designed a set of roll position automatic adjustment system that can predict roll parameters by using PCA-BP algorithm to train roll parameter prediction model, so as to predict roll parameters of newly developed square tube cold roll forming distribution. Bidabadi et al [12] studied the in uence of bend angle increment, ange width, strip thickness, bending radius and material strength on over-bending defect ground by combining multiple groups of test and numerical simulation. Therefore, the appropriate cold roll forming process is also an important guarantee for the precise forming of circular tubes of different speci cations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] With the continuous development and maturity of finite element simulation technology, more and more scholars today were using finite element analysis to study the deformation process of sheets. 5,6 Finite element simulation also plays an important role in the study of part springback. Sun et al 7 found that the hot forming of high-strength steel significantly reduced springback by about 62% compared to cold forming through the finite element model developed and also found that rapid forming was beneficial in reducing springback.…”
Section: Introductionmentioning
confidence: 99%
“…Over-bending in the open section of the panels may also diminish their overall quality and trigger other defects such as edge wrinkling. 5 Other manufacturing solutions based on conventional forming of grooves with punch and die sets 6,7 are limited by the time and cost to fabricate the tools and because these are dependent on the geometry of the panels. Despite electromagnetic forming allows one element of the tool set (usually the punch) to be replaced by a coil, this process variant is limited to highly conductive materials, to small size panels and cannot avoid the groove geometry dependence of the dies.…”
Section: Introductionmentioning
confidence: 99%
“…Over-bending in the open section of the panels may also diminish their overall quality and trigger other defects such as edge wrinkling. 5…”
Section: Introductionmentioning
confidence: 99%